The Relationship between Self Efficacy with First Aid Behavior of Traffic Accident Victims of Zona Persada Nursing Students in Tuban DIstric - Faqih, Moh. Ubaidillah; Nasrul; Hufana, Only (Babali Publisher, 2023)
A B S T R A C T Background: First aid in an accident is a knowledge and skill that must be possessed by everyone in helping accident victims. In this case, the community as the first person at the scene must have the knowledge and attitude to be alert in first aid, because first aid for patients is very important. determine a disability or death consideration. Objective: The sampling technique used probability sampling with cluster random sampling, so the total sample taken in this study was 135 students consisting of 4 regions namely Palang, Tuban Kota, Semanding, and Widang in the PERSADA zone area. The collection method uses a questionnaire from the variables of self-efficacy and accident first aid behavior. Methods: This type of research is non-experimental with correlation analytical design with cross sectional time approach. Results: The results of the research were carried out after being analyzed using the Spearman's test with a significance level of α = <0.05, obtained a value = 0.000 <0.05 with a correlation coefficient of r = 0.932 which shows the relationship between the two variables is included in the strong category, so H1 is accepted. Conclusion: It can be concluded that there is a significant relationship between flood preparedness and community resilience with the strength of the relationship between the two variables included in the strong category with a positive direction. KEYWORDS: Flood Disaster Preparedness, Resilience, Residents